PENERAPAN METODE PEMBELAJARAN INKUIRY LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR BIOLOGI LINTAS MINAT SISWA KELAS XII IPS 3 TAHUN PELAJARAN 2021/2022 DI SMAN I PURWANTORO - Siti Ruliyah (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The aim of this action research is to find out the implementation of Inquiry-based learning, to know the improvement of activeness and learning outcomes of biology cross -interest students of XII IPS 3 academic year 2021/2022 at SMAN 1 Purwantoro as a result of the implementation of Inquiry-based learning in cross-interest biology subjects with Growth and Growth of Plants. The type of this research is Classroom Action Research (CAR) which consists of two cycles, each cycle consisting of 4 stages Planning, Action, Observation, and Reflection. The subjects of this study were students of class XII IPS 3 academic year 2021/2022 of SMAN 1 Purwantoro, totaling 34 students. Data collection instruments include the result of observations of the implementation of inquiry-based learning, the assessment of studentsinquiry products, the results of observations of students activity and the results of post-test cycles1 and cycles 2. The data analysis technique was carried out with descriptive qualitative based on research data obtained in cycle 1 and cycle 2. The results showed (1) an increase in the implementation of the learning process. In cycle 1 learning accomplishments were 71.3% while in the cycle 2 is increased to 86%, (2) an increase in students inquiry products, in cycle 1 the average value of inquiry products was 75 while cycle 2 reached 85. (3) an increase in students activity, in cycle 1 students activity reached 74% while cycle 2 reached 85%, (4) an increase in cross-interest biology learning outcomes, in cycle 1 completeness reached 63% cycle 2 reached 83%. The mean value of cycle 1 reached 64 while cycle 2 reached 75.